'Making it Count': Incentives, Student Effort and Performance. (18th April 2017) - Chevalier, Arnaud; Dolton, Peter; Lührmann, Melanie
Summary: The paper examines how incentives to participate in on-line assessments (quizzes) affect students' effort and performance. Our identification strategy exploits within-student weekly variation in incentives to attempt on-line quizzes. We find that tournament incentives and participation incentives are ineffective in increasing quiz participation. In contrast, making the quiz count towards the final grade substantially increases participation. We find no evidence of displacement of effort between weeks. Using a natural experiment which provides variation in assessment weighting of the quizzes between two cohorts, we find that affected students obtain better examination grades. We estimate the return to 10% assessment weighting to be around 0.27 of a standard deviation in the in-term examination grade. We find no evidence that assessment weighting has unintended consequences, i.e. that increased quiz effort displaces effort over the year, reduces other forms of effort or reduces (effort and thus) performance in other courses. Finally, assessment weighting induced effort increases most for students at and below median ability, resulting in a reduction of the grade gap by 17%.